An Observational Study of Intravenous Dexmedetomidine and Clonidine for Attenuating Haemodynamic Response to Laryngoscopy and Intubation in Patients Undergoing General Anaesthesia - Priya Kishnani; Sanam Shah; Jayshri Desai; Anuja Agrawal (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Laryngoscopy and endotracheal intubation alters cardiovascular physiology causinghypertension and tachycardia. Dexmedetomidine, an alpha 2 adrenergic receptor produces analgesiaby direct activation of descending inhibitory pain pathway and inhibiting the release of substance P.Clonidine a centrally acting alpha 2 adrenergic agonist decreases central sympathetic nervous system in allhyperadrenergic situations. Hence we compare haemodynamic effects between dexmedetomidine 0.5 mcg/kg and clonidine 1mcg/kg during after laryngoscopy and tracheal intubation for patients undergoing generalanaesthesia.Method: Patients were allocated randomly into 2 groups of 30 each. Group D received dexmedetomidine0.5mcg/kg diluted in 10ml NS and group C- clonidine 1 mcg/kg diluted in 10ml NS intravenously andhemodynamic parameters were observed. Dexmedetomidine/ Clonidine according to groups is givenintravenously with premedication. After 5 minutes patients were induced with 2.5% thiopentone 5-7 mg/kgand succinyl choline 2mg/kg and intubated with appropriate sized cuffed ETT. Anaesthesia was maintainedwith O2, N2O, isoflurane and vecuronium bromide 0.08mg/kg.Results: Haemodynamic changes after laryngoscopy and intubation were recorded at baseline, premedication,induction, intubation, 1, 3, 5,10 and 15 minutes. The initial fall in HR is more in Group C compared to GroupD but the difference was insignificant, but since intubation till 10min post intubation HR was significantly(p<0.05) supressed more in Group D. Similarly fall in SBP and DBP is significantly (p<0.05) more in GroupD compared to Group C.Conclusion: Dexmedetomedine 0.5 mcg/kg intravenously 15 minutes prior to laryngoscopy and intubationattenuates the sympathetic response better as compared to clonidine without major side effects.